PEMBELAJARAN KOLABORATIF SEBAGAI UPAYA UNTUK MENINGKATKAN HASIL BELAJAR DI MI UIN SUNAN GUNUNG DJATI BANDUNG - Muhammad Rakha Fauzan; Muhamad Mugni Sahid; Ibnu Laksana Aulia Ramdani; Qiqi Yuliati Zaqiah; Uus Ruswandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to measure the difference in effectiveness between collaborative learning and conventional learning models in improving student learning outcomes in Tahsin subjects at MI Sunan Gunung Djati Bandung. Quantitative approach with quasi experimental design was used in this study, involving class II Thalhah as the treatment group (collaborative learning) and class II Zubair as the control group (conventional). Data analysis was conducted using the Mann-Whitney test because the data was not normally distributed based on the results of the Shapiro-Wilk test. The results showed that the average student learning outcomes in the collaborative learning model were higher than conventional learning. However, the difference was not statistically significant (Sig. 2-tailed value = 0.138 > 0.05). This finding indicates that there is no significant difference between the two learning models in improving student learning outcomes. Internal factors such as student motivation and external factors such as limited learning facilities are thought to have influenced the results of this study. This study concludes that learning effectiveness does not only depend on the learning model used, but is also influenced by various other factors such as facility support, teacher teaching methods, and students' learning motivation conditions.